2004
DOI: 10.1094/mpmi.2004.17.4.383
|View full text |Cite
|
Sign up to set email alerts
|

CPTF1, a CREB-Like Transcription Factor, Is Involved in the Oxidative Stress Response in the Phytopathogen Claviceps purpurea and Modulates ROS Level in Its Host Secale cereale

Abstract: CPTF1, a transcription factor with significant homology to ATF/CREB bZIP factors, was identified during an expressed sequence tag (EST) analysis of in planta-expressed genes of the phytopathogen Claviceps purpurea. Using a gene-replacement approach, deletion mutants of cptf1 were created. Expression studies in axenic culture showed that the H2O2-inducible gene cpcat1 (encoding a secreted catalase) had a reduced basal expression level and no longer responded to oxidative stress in the delta cptf1 mutant. Bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 56 publications
6
67
1
2
Order By: Relevance
“…Thus, the Yap1-controlled ROS detoxification system serves an important function during the early U. maydis infection phase. In the Claviceps purpurea/rye interaction it has been demonstrated that the deletion of a CREBlike transcription factor, CPTF1, which positively controls catalase production, also induces an oxidative burst (Nathues et al, 2004) similar to what we have observed in yap1 mutants of U. maydis. However, in this case, it is speculated that CPTF1 negatively controls the activity of a fungal NADPH oxidase (i.e., when CPTF1 is deleted, the fungus would produce elevated levels of H 2 O 2 , which then in turn would trigger the oxidative burst) (Nathues et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…Thus, the Yap1-controlled ROS detoxification system serves an important function during the early U. maydis infection phase. In the Claviceps purpurea/rye interaction it has been demonstrated that the deletion of a CREBlike transcription factor, CPTF1, which positively controls catalase production, also induces an oxidative burst (Nathues et al, 2004) similar to what we have observed in yap1 mutants of U. maydis. However, in this case, it is speculated that CPTF1 negatively controls the activity of a fungal NADPH oxidase (i.e., when CPTF1 is deleted, the fungus would produce elevated levels of H 2 O 2 , which then in turn would trigger the oxidative burst) (Nathues et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…Other transcripts with potential roles in metabolism of reactive oxygen species or redox homeostasis included a putative Cu/Zn superoxide dismutase, a catalase (1-L10-SP6/T7) and a homologue of the cAMP response element (CREB-like) transcription factor CPTF1, which regulates catalase activity and contributes to virulence in the biotrophic plant pathogen Claviceps purpurea (Nathues et al, 2004).…”
Section: Putative Virulence and Pathogenicity Genesmentioning
confidence: 99%
“…By comparing with superoxide (O 2 •), hydroxyl radical (•OH) and other ROS, H 2 O 2 is the most stable compound (Cheeseman 2007). Within the cellular concentration, H 2 O 2 behaves as a signaling molecule and it is used for the induction of gene expression, helpful for physiological process (Nathues et al 2004). H 2 O 2 becomes more dangerous when it reacts with some transition metals as Fe 2+ and produces two molecules of OH -by Fenton reaction (Becana et al 1998).…”
Section: Introductionmentioning
confidence: 99%